2017
DOI: 10.1122/1.4991803
|View full text |Cite
|
Sign up to set email alerts
|

The yielding and the linear-to-nonlinear viscoelastic transition of an elastoviscoplastic material

Abstract: Elastoviscoplastic materials present a transition from a gel-like to a liquidlike state induced by shearing: While the first is primarily elastic, the second is predominantly viscous. The point that characterizes this transition is usually known as the yield point, which is associated to critical quantities such as yield stress and/or yield strain. Another characteristic of elastoviscoplastic materials is the transition from linear to nonlinear viscoelasticity. In the current work, a commercial hair gel, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 87 publications
2
52
0
Order By: Relevance
“…This has led to the predominant description of yielding as being a binary phenomenon, as evidenced by the ubiquity of models in existence with a single yield stress (5,(16)(17)(18)(19)(20). There have been challenges to the existence of a yield stress in the past (5,21), and a number of recent studies (22)(23)(24) have explicitly shown that attempts to define a single yield threshold are ambiguous, at best. Furthermore, the fact that Bingham chose to only investigate the steady-state properties of plastic materials, and did not consider any time dependence, led to the furtherance of the idea that yielding is an instantaneous phenomenon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to the predominant description of yielding as being a binary phenomenon, as evidenced by the ubiquity of models in existence with a single yield stress (5,(16)(17)(18)(19)(20). There have been challenges to the existence of a yield stress in the past (5,21), and a number of recent studies (22)(23)(24) have explicitly shown that attempts to define a single yield threshold are ambiguous, at best. Furthermore, the fact that Bingham chose to only investigate the steady-state properties of plastic materials, and did not consider any time dependence, led to the furtherance of the idea that yielding is an instantaneous phenomenon.…”
mentioning
confidence: 99%
“…It is now known that the transition requires a finite amount of time to complete (23). As a result, it has been difficult to develop an understanding of the processes and mechanisms (both rheological and microstructural) that occur during yielding (5,7,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). This has, in turn, reduced the availability or development of structure-property relations for the yielding transition, which has rendered the tailored design of novel plastic soft materials difficult (10,11).…”
mentioning
confidence: 99%
“…Fully immersed the vane rotor in the slurry and rotated at a constant speed, the shear stress was measured as a function of shear strain or time as shown in Figure 2. e curve was divided into two parts: AB segment was the stress rise phase which was the initial structural failure process [20][21][22] and BC segment was the stress decay phase which was the thixotropic process [23,24].…”
Section: Mechanical Properties Andmentioning
confidence: 99%
“…Consequently, we can extend the definition of the yield stress to include all rheological systems-the rheological systems must have a three-dimensional network at low shear rates, but it is not necessary to be an elastic solid. The yield stress can be determined from the region of the flow curve, where the shear stress does not change significantly with the increase of the shear rate [19,[21][22][23][24][25][26][27] by extrapolation of the shear stress to the y-axis.…”
Section: Determination Of the Yield Stress Of Disperse Systems 150mentioning
confidence: 99%